Faces of Aeneas. Representations on Roman Coins and Medallions - Kluczek, Agata A. (Studia Ceranea, 2016)
On the basis of numismatic material I present aspects of the figure of Aeneas as they appear in ancient tradition. I have concentrated on the iconographic details and the arrangement of the reverse scenes which allow one to isolate the elements of Aeneas’s portrait in the coinage that are closely associated with his role as the one who, by carrying over the sacra to Italy, made way for the foundation and continuation of Rome.